Strategi Pemasaran dalam Meningkatkan Kunjungan Wisatawan pada PHD Nusantara - Zuvilla Alfin Monica; Muhammad Alhada Fuadilah Habib (Universitas 45 Surabaya, 2024)
Marketing strategy has an important role in business success. Companies are able to attract consumer attention through the right marketing strategy. PHD Nusantara is an artificial tourist attraction with traditional Balinese and Javanese nuances. Based on a preliminary survey, PHD Nusantara was able to implement appropriate marketing strategies, so that its business developed and succeeded in increasing interest in tourist visits. The aim of this research is to describe marketing strategies to increase tourist visits to PHD Nusantara. This research uses a qualitative descriptive research type. Data collection techniques using interviews, observation and documentation. The technique for determining informants in this research uses a purposive technique. Data analysis includes data collection, data coding, data presentation and drawing conclusions. Checking the validity of the data uses technical triangulation and source triangulation. Based on the research that has been carried out, the results obtained are that the marketing strategy carried out by PHD Nusantara has succeeded in increasing tourist visits by implementing the 7P marketing mix strategy (product, price, place, promotion, people, process, physical evidence), namely, providing unique photo spots, provides culinary delights that are varied and delicious, offers education on traditional arts and culture, provides vendors for various events, has a mini water park and playground. Providing affordable prices according to quality. Has a comfortable, clean and easy to access design. Promotion through word of mouth, placing banners, distributing brochures and using social media such as Instagram, Facebook, WhatsApp. Provide training to all employees and apply the 3S rules (smile, greet and greet) in serving customers. Providing excellent service in the ticket purchasing process, food ordering process and the tour guide process in guiding education. Provide physical evidence in the form of buildings and ornaments with traditional Balinese and Javanese nuances.